Orthoflavivirus Lammi in Russia: Possible Transovarial Transmission and Trans-Stadial Survival in Aedes cinereus (Diptera, Culicidae) - Kholodilov, Ivan S.; Aibulatov, Sergey V.; Khalin, Alexei V.; Polienko, Alexandra E.; Klimentov, Alexander S.; Belova, Oxana A.; Rogova, Anastasiya A.; Medvedev, Sergey G.; Karganova, Galina G. (Viruses, 2024)
In the last few years, there has been a dramatic increase in the number of discovered viruses that are transmitted by arthropods. Some of them are pathogenic for humans and mammals, and the pathogenic potential of others is unknown. The genus Orthoflavivirus belongs to the family Flaviviridae and includes arboviruses that cause severe human diseases with damage to the central nervous system and hemorrhagic fevers, as well as viruses with unknown vectors and viruses specific only to insects. The latter group includes Lammi virus, first isolated from a mosquito pool in Finland. It is known that Lammi virus successfully replicates in mosquito cell lines but not in mammalian cell cultures or mice. Lammi virus reduces the reproduction of West Nile virus during superinfection and thus has the potential to reduce the spread of West Nile virus in areas where Lammi virus is already circulating. In this work, we isolated Lammi virus from a pool of adult Aedes cinereus mosquitoes that hatched from larvae/pupae collected in Saint Petersburg, Russia. This fact may indicate transovarial transmission and trans-stadial survival of the virus.